Research on the generation mechanism and interference of surface texture in ultrasonic vibration assisted milling. (15th October 2021) - Lu, Hao; Zhu, Lida; Yang, Zhichao; Lu, Hao; Yan, Boling; Hao, Yanpeng; Qin, Shaoqing
Highlights : Based on generation mechanism of surface texture in UVAM, the shape and dimension of texture are designed quantitatively. A "step-increment" simulation method is proposed to predict the surface texture. The study of interference among textures is proposed for the first time. The relationship between the generation accuracy and machining parameters of the surface texture is revealed. Abstract: Functional microstructure surfaces exhibit excellent performance in many interfacial contact fields. Owing to high-frequency periodic vibration applied to the machining path, the surface texture generated by ultrasonic vibration assisted milling (UVAM) has unique characteristics. Besides, the texture generation mechanism is still unclear because of the complicated interaction of machining parameters, which limits application of UVAM. In this paper, the surface texture generation mechanisms including ultrasonic vibration end milling (UVEM) and ultrasonic vibration peripheral milling (UVPM) are systematically studied. The shape and dimension of textures were designed by analytical calculation. In addition, the corresponding parameters were determined by an established parameters selection model. The effect of interference on surface texture generation is studied for the first time in UVAM, and the texture topography after interference was also characterized. Furthermore, a "step-increment" discrete simulation model was developed to predict the topography of typical textures and interference textures. For improving the accuracy of texture topography prediction, the profile of cutting edge was also considered into the simulation model according to coordinate transformation. Then, the UVAM experiments were carried out on difficult-to- machine materials (Ti6AL4V) to verify the accuracy of numerical design, surface simulation and texture generation. The relationship between the machining quality and the ultrasonic milling parameters was also revealed. In addition, the wettability of surface textures was observed. The results indicated that the micro textures generated by UVAM contribute to the interface modification. To sum up, the research on the texture generation and interference in UVAM can expand the scope of application in the field of interface contact. Graphical abstract: Image, graphical abstract